Two Imported Malaria Cases with Delayed Response to Treatment in Hatay - Tuğba Kaya; Mehmet Çabalak; Gülnaz Çulha; Ceren Ünal (Türkiye Parazitoloji Dergisi, 2024)
The study presents two imported malaria cases with a history of travel to malaria-endemic areas and replied late response to treatment. In the blood preparations of the first case, dot-shaped nucleus structures were identified in the erythrocytes, which looked different from the classical erythrocytic forms. In the SD-Pf/Pan test, bands were obtained for both P.f and Pan; while in the SD-Pf/Pv test, a band was obtained for P.f. The P. falciparum18S rRNA gene was detected using real-time polymerase chain reaction. Artemether-lumefantrine treatment protocol was started. Due to deterioration in general condition on the third day, artemether-lumefantrine treatment was extended to six days, and primaquine phosphate was added. Discharge was on the 16th day of treatment. In the second case, young trophozoites were identified in blood smears. Bands in P.f were obtained in both the SD-Pf/Pan and SD-Pf/Pv tests. Artemether-lumefantrine treatment protocol was started. On the third day of treatment, banana-like gametocytes were observed in blood smears. The patient was discharged at his own request and two days later, upon follow-up, gametocytes were still observed in blood smears. Artemether-lumefantrine treatment was restarted. Gametocytes continued to be observed in the following days. Primaquine phosphate was added to the treatment protocol. The patient was discharged after a 3-week follow-up. The study is presented to draw attention to the increasing cases of imported malaria in Hatay and the increase of malaria cases that respond late to treatment in recent years.